Human G109E-inhibitor-1 impairs cardiac function and promotes arrhythmias. (December 2015) - Haghighi, Kobra; Pritchard, Tracy J.; Liu, Guan-Sheng; Singh, Vivek P.; Bidwell, Philip; Lam, Chi Keung; Vafiadaki, Elizabeth; Das, Parthib; Ma, Jianyong; Kunduri, Swati; Sanoudou, Despina; Florea, Stela; et al.
Abstract: A hallmark of human and experimental heart failure is deficient sarcoplasmic reticulum (SR) Ca-uptake reflecting impaired contractile function. This is at least partially attributed to dephosphorylation of phospholamban by increased protein phosphatase 1 (PP1) activity. Indeed inhibition of PP1 by transgenic overexpression or gene-transfer of constitutively active inhibitor-1 improved Ca-cycling, preserved function and decreased fibrosis in small and large animal models of heart failure, suggesting that inhibitor-1 may represent a potential therapeutic target. We recently identified a novel human polymorphism (G109E) in the inhibitor-1 gene with a frequency of 7% in either normal or heart failure patients. Transgenic mice, harboring cardiac-specific expression of G109E inhibitor-1, exhibited decreases in contractility, Ca-kinetics and SR Ca-load. These depressive effects were relieved by isoproterenol stimulation. Furthermore, stress conditions (2 Hz +/− Iso) induced increases in Ca-sparks, Ca-waves (60% of G109E versus 20% in wild types) and after-contractions (76% of G109E versus 23% of wild types) in mutant cardiomyocytes. Similar findings were obtained by acute expression of the G109E variant in adult cardiomyocytes in the absence or presence of endogenous inhibitor-1. The underlying mechanisms included reduced binding of mutant inhibitor-1 to PP1, increased PP1 activity, and dephosphorylation of phospholamban at Ser16 and Thr17. However, phosphorylation of the ryanodine receptor at Ser2808 was not altered while phosphorylation at Ser2814 was increased, consistent with increased activation of Ca/calmodulin-dependent protein kinase II (CaMKII), promoting aberrant SR Ca-release. Parallel in vivo studies revealed that mutant mice developed ventricular ectopy and complex ventricular arrhythmias (including bigeminy, trigeminy and ventricular tachycardia), when challenged with isoproterenol. Inhibition of CaMKII activity by KN-93 prevented the increased propensity to arrhythmias. These findings suggest that the human G109E inhibitor-1 variant impairs SR Ca-cycling and promotes arrhythmogenesis under stress conditions, which may present an additional insult in the compromised function of heart failure carriers. Highlights: Naturally occurring human G109E inhibitor-1 (I-1) impairs cardiac function. G109E I-1 exhibits diminished PP1 inhibition, resulting in PLN dephosphorylation. Depressed SR Ca uptake increases diastolic Ca, CaMKII activity and pSer2814 in RyR2. Hyperphosphorylated RyR2 increases the frequency of Ca-sparks and Ca-waves. G109E I-1 leads to aftercontractions and arrhythmias under stress conditions.